Darwin Koenig letter to Nicholas S. Halmi regarding bird sightings - Koenig, Darwinet al (1977)
Letter from Darwin Koenig to Nicholas S. Halmi regarding winter bird sightings.This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter, 1977-1978. Epson - sheet feed/flatbed